THE ACCURACY OF DIAGNOSIS, PROCEDURES AND CODING COMPLETENESS AND THEIR CORRELATION WITH INA-CBG CLAIMS - Yuliani Yuliani; Atik Nurwahyuni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Since 1 January 2014, the INA-CBG system has been applied as a method of payment for outpatient and inpatient services. Indonesian-Case Based Groups (INA-CBG) tariff is the amount of payment claimed by the Health Social Security Administering Agency (BPJS) to the hospitals for a package of services based on the classification of diagnoses and procedures of diseases. The inequality in the number of claims received by the hospital compared to the resources used will be unbeneficial to the hospital. The purpose of this study is to identify the correlation of incompleteness and inaccuracy of diagnosis, procedures, and coding to the number of INA-CBG claims at hospitals in Indonesia. Method: The research method is the literature review. The authors found five articles cited by Google Scholar published in journals and two theses taken from the Library of Universitas Indonesia that include ”factors that influence INA-CBGs claim amounts at hospitals” or related concepts in the title or abstract. Articles and theses published from 2014 to 2018 were search using the following terms in the title or abstract: “accuracy, completeness, diagnosis, coding, INA-CBG claims.”.Result: The authors found seven articles that met our criteria: Two studies used qualitative approach, three studies were quantitative studies, two studies used a mix method. From these studies, there were five practical considerations that were considered as the factors that influenced the number of INA-CBGs claims at hospitals in Indonesia: completeness of filling a medical resume, accuracy of coding, accuracy in filling medical resumes, the accuracy of information systems, and completeness of claim administration document.Conclusion: The study has indicated the factors that influence the amount of INA-CBG claims in hospitals in Indonesia, mainly, the factor of completeness of medical resumes and the factor of accuracy in coding by the coders. The completeness of a medical filling resume which is highly dependent on physician compliance and accuracy coding. All the human resources who have a role in coding and claims, need to improve their capability on it, through a workshop, or any other education funded by the hospital. Coder certification must be done. Hospital has to develop hospital management information system for acceleration in coding and claim.